The Effective Management of Municipal Real Property. The Question of Services for the Business Use of Real Property - Daniela Luminiţa Constantin; Mariana Drăguşin; Raluca Mariana Petrescu; Alina Elena Iosif (Amfiteatru Economic Journal, 2012)
The paper proposes a comparative analysis of three different scenarios for the efficient use of the former Bucharest City Hall building (BCHb) for business purpose. All three scenarios are related to the area of services, namely real estate, retail, cultural services and hotel services. In order to expose the scenario that leads to the best use of the former BCHb a classical model of development appraisal was elaborated. For each scenario, market and financial analysis were conducted. In order to obtain a complex and well documented pre – feasibility study regarding the BCHb three scenarios have been designed, as follows: the first is a mix between offices at the upper levels and retail space at the ground floor of the BCHb; the second is composed of offices at the upper levels and museum at the ground floor; and the third scenario is projected for hotel destination. Starting from the national perspective and continuing with the analysis up to the particular area of the BCHb, the major characteristics of the office, retail and hotel markets were revealed. The financial analysis implied calculations of the most representative indicators used in this type of study, such as net present value, internal rate of return or payback period. Considering the financial indicators comparison, the pre-feasibility study pointed out that the BCHb should follow the scenario with the mix between offices and retail space.
Keywords: R38; R52; R53; R58; 330; municipal real property; management of municipal real property; pre – feasibility study; business use; services